Patterns of plant organ-level non-structural carbohydrate content in response to nitrogen and phosphorus enrichment - Zhou, Weiyi; Gu, Peirui; Tang, Yuejuan; Zhang, Yuanming (Frontiers in Plant Science, 2025)
Carbon is one of the most crucial elements within plants, with its production and supply determining growth behaviors and physiological strategies. Nonstructural carbohydrates (NSC) serve as the “currency” of plant carbon flow, playing a key role in the balance between structural growth and carbon storage. However, the response patterns of NSC pools to varying concentrations and durations of nitrogen and phosphorus enrichment remain unclear. We conducted a meta-analysis compiling 1,313 independent data points from four plant organs-leaves, branches, stems, and roots-across global experiments to evaluate the impact of N and P enrichment on NSC pools in different organs. Our findings indicate that N limitation is widespread in ecosystems, whereas P limitation is not. Both the concentration and duration of N enrichment exhibit significant threshold effects on NSCs. Low to moderate levels of N enrichment led to varied increases in soluble sugar content (0.24% to 19.14%) and decreases in starch content (1.22% to 32.35%) in the leaves and branches of woody plants. However, this trend weakened or disappeared at high N concentrations. The NSC content in herbaceous plants was more sensitive to nutrient enrichment, with N enrichment significantly reducing their NSC reserves across all organs (by up to 90.72%). By integrating global data, this study not only addresses the gaps left by individual experiments in elucidating the spatio-temporal threshold responses of NSC to nutrient enrichment but also reveals the scarcity of studies on P addition and of long-term experiments in the existing literature. It reveals the growth-carbon storage strategies of plants under different nutrient conditions, contributing to biodiversity conservation and resource utilization in the context of future nitrogen deposition.